2020
DOI: 10.1002/dmrr.3295
|View full text |Cite
|
Sign up to set email alerts
|

Different β‐cell secretory phenotype in non‐obese compared to obese early type 2 diabetes

Abstract: Background: Type 2 diabetes (T2D) is characterized by impaired tissue sensitivity to insulin action (ie, insulin resistance) and impaired β-cell insulin secretion. Because obesity contributes importantly to the development of insulin resistance, we sought to determine whether insulin secretory defects would predominate in non-obese compared to obese T2D. Methods:We measured β-cell function and secretory capacity using the glucose-potentiated arginine test in T2D subjects early in the disease course classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Emerging evidence indicates that obese (i.e., BMI more than 30 kg/m 2 ) and non-obese people with diabetes have different metabolic profiles. For example, a 2020 clinical study investigating insulin sensitivity (with the use of a hyperinsulinemic-euglycemic clamp) of non-obese versus obese individuals with T2DM demonstrated that insulin sensitivity (determined by the ratio of metabolic rate to steady-state insulin) was more than two-times greater in non-obese than obese individuals with T2DM (p < 0.05) [21]. Another clinical study using a clamp technique to investigate glucose metabolism in non-obese versus obese individuals with T2DM also showed significant differences in insulin sensitivity (i.e., insulin sensitivity index, p < 0.01) and insulin secretion (i.e., fasting C-peptide response, p < 0.05) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates that obese (i.e., BMI more than 30 kg/m 2 ) and non-obese people with diabetes have different metabolic profiles. For example, a 2020 clinical study investigating insulin sensitivity (with the use of a hyperinsulinemic-euglycemic clamp) of non-obese versus obese individuals with T2DM demonstrated that insulin sensitivity (determined by the ratio of metabolic rate to steady-state insulin) was more than two-times greater in non-obese than obese individuals with T2DM (p < 0.05) [21]. Another clinical study using a clamp technique to investigate glucose metabolism in non-obese versus obese individuals with T2DM also showed significant differences in insulin sensitivity (i.e., insulin sensitivity index, p < 0.01) and insulin secretion (i.e., fasting C-peptide response, p < 0.05) [22].…”
Section: Introductionmentioning
confidence: 99%
“…β-cell secretory capacity provides the best estimate of functional β-cell mass and is measured from glucose-potentiation of insulin or C-peptide release in response to a non-glucose secretagogue, such as arginine ( 22 ). In advanced type 2 diabetes (T2D), β-cell secretory capacity is diminished without a change in β-cell sensitivity to glucose ( 23 , 24 ), while early in T2D impaired β-cell sensitivity to glucose is present with relative preservation of the reserve capacity for insulin secretion that is evident with maximal glucose-potentiation ( 25 ). In contrast, we have demonstrated a decrease in β-cell secretory capacity in PI-CF subjects that progresses with worsening glucose tolerance status without any impairment in β-cell sensitivity to glucose ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of an association of PIR with glucose metabolism that is independent of the metabolic syndrome is supported by a recent study showing increased proinsulin secretory ratios in non-obese participants with T2D compared with obese participants with T2D in response to a glucose-potentiated arginine test. 28 In turn, high HOMA-IR, indicating insulin resistance (eg, in overweight or obesity), may initially be related to a low PIR in pre-diabetes or NGT, resulting from a compensatory hypersecretion of insulin, whereas proinsulin levels initially remain constant, leading to a decreased or normal PIR. 17 29 30 At a later stage, when β-cell failure and T2D become apparent, proinsulin levels will increase disproportionately, resulting in an elevated PIR.…”
Section: Discussionmentioning
confidence: 99%